If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + x + 6x = 119 + 6x Combine like terms: x + x = 2x 2x + 6x = 119 + 6x Combine like terms: 2x + 6x = 8x 8x = 119 + 6x Solving 8x = 119 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 8x + -6x = 119 + 6x + -6x Combine like terms: 8x + -6x = 2x 2x = 119 + 6x + -6x Combine like terms: 6x + -6x = 0 2x = 119 + 0 2x = 119 Divide each side by '2'. x = 59.5 Simplifying x = 59.5
| 6x+8=-4x | | 3x=-2x-5 | | 5x+15/5=35-x | | 6x+8=11-4x | | 2x^3-5x=27 | | 4*x+43+2*x=7 | | (0.3+2x)(0.5+2x)=5.3018 | | -9*x-2*x-18=26 | | 108+(5x+8)=x | | -(9-3a)-(4+2a)-3=-(2-5a)+(-a)+1 | | x/2+x/4+x/5=x-1 | | w*5-7+w*2=-17 | | 3*3=8 | | 48-54+30= | | 63x^2-24x-15=0 | | -9(9-3a)-(4+2a)-3=-(2-5a)+(-a)+1 | | q^2+4q+4=26 | | 6-+4=210 | | 3x+20=5-16 | | (3x-4)(x-3x+2)= | | x/30=9 | | 16=s-p | | 12v^2+12v-15=0 | | 72-4.9t^2=8t | | 4x-4=-48 | | 3/10+7/10 | | 0-600*2-600*2+X*2-0.2X*4=0 | | a^2-a-8=0 | | 7/10+1/5 | | 4x+7-3x=15 | | -4n+2+3n=8-n+6 | | 5/12+5/12 |